ANALISIS HUBUNGAN USIA DAN PARITAS DENGAN UPAYA PREVENTIF TRANSMISI COVID-19 : Analysis of the Relationship between Age and Parity with Preventive Efforts for Covid-19 Transmission - Anggun Fitri Handayani; Karlinda; Santy Irene Putri; Agnis Sabat Kristiana; Arie Jefry Ka’arayeno; Aris Widiyanto; Joko Tri Atmojo (Forind Press, 2024)
The COVID-19 virus affects the immune system of pregnant women, especially for respiratory infections. So, it is important for pregnant women to take precautions to protect themselves from COVID-19, and to report any symptoms that may appear (including fever, cough, or difficulty breathing) to a healthcare provider. this study aims to investigate the relationship between age and parity with Coronavirus-19 prevention habits in pregnant women. A cross-sectional study design conducted in West Kalimantan from August to September 2020 on 43 pregnant women. The dependent variable in this study is preventive behavior for coronavirus (COVID-19). The Independent variables are age and parity. Interview-based questionnaire were used to obtain data. Pearson correlation was used to analyze the association between age and parity with Coronavirus-19 prevention habits in pregnant women. Age (r=0.44; p=0.015) and parity (r=0.49; p=0.006) has correlation in Coronavirus-19 prevention habits in pregnant women. The more mature the age of the pregnant woman, the behavior in preventing transmission of the COVID-19 virus will be better because she gains more experience. Pregnant women with more than one parity have better knowledge and more experience about pregnancy so that they will protect their pregnancy from the risk of COVID-19 infection.